Snail Expression is Positively Correlated with Depth of Invasion in Colorectal Carcinoma - Miskad, Upik Anderiani; Akil, Fardah; Cangara, Muhammad Husni; Dahlan, Haslindah; Hutasoit, Gina Andyka; Ilyasa, Muhammad Riza (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Colorectal carcinoma ranks as the second deadliest and third most prevalent cancer globally. The depth of tumor invasion and the presence of tumor-infiltrating lymphocytes (TILs) are linked to survival rates in this disease. Meanwhile, Snail expression is positively correlated with tumor grade, recurrence, metastasis and poor prognosis in various tumors. However, not many studies discuss the correlation of Snail expression with invasion depth and TILs in Indonesia. Therefore, this study was conducted to investigate the correlation between Snail expression and both the depth of invasion and TIL scoring in colorectal carcinoma.METHODS: A cross-sectional study was conducted to evaluate 70 paraffin-embedded blocks of colorectal carcinoma patients. Snail expression was measured with immunohistochemistry using Snail rabbit polyclonal antibody. Stromal TILs were assessed on a single full-face hematoxylin and eosin (H&E) slide, and classified into high, intermediate, and low TILs.RESULTS: The results showed that the most invasion was to the muscularis propria (42.9%) and the least invasion was to the submucosa (4.3%). In scoring TILs, the most samples with intermediate TILs (58.6%) and the least samples with low TILs (4.3%). The analysis employing a Spearman Rank coefficient shows significant positive correlation between the expression of Snail with depth of invasion (r=0.273; p=0.022) but there was no significant correlation with TILs scoring (p=0.892).CONCLUSION: Even though, there is no significant correlation between Snail expression with TILs, there is, however, a significant positive correlation between Snail expression with depth of invasion in colorectal carcinoma. Therefore, Snail expression might be potentially used as a prognostic factor in colorectal carcinoma.KEYWORDS: Colorectal, carcinoma, Snail, depth of invasion and TILs